Self‐Assembly of Copolymers Containing Crystallizable Blocks: Strategies and Applications - Shi, Boyang; Shen, Ding; Li, Wei; Wang, Guowei (Macromolecular rapid communications., 2022)
The self‐assembly of copolymers containing crystallizable blocks in solution has received increasing attention in the past few years. Various strategies including crystallization‐driven self‐assembly (CDSA) and polymerization‐induced CDSA (PI‐CDSA) have been widely developed. Abundant self‐assembly morphologies are captured and advanced applications have been attempted. In this review, the synthetic strategies including the mechanisms and characteristics are highlighted and a survey on the advanced applications of crystalline nano‐assemblies is collected. This review is hoped to depict a comprehensive outline for self‐assembly of copolymers containing crystallizable blocks in recent years and to prompt the development of the self‐assembly technology in interdisciplinary fields. Over the last few years, crystallization‐driven self‐assembly (CDSA) and polymerization‐induced CDSA (PI‐CDSA) have been widely utilized in preparing nano‐objects containing crystallizable blocks. These nano‐objects with various architectures have been applied to multiple fields. This review focus on the strategies and applications of self‐assembly of copolymers containing crystallizable blocks.